Case reportCardiac arrest due to left circumflex coronary artery embolism as a complication of subtherapeutic oral anticoagulation in a patient with mitral and aortic mechanical valve prostheses - Protasiewicz, Marcin; Rojek, Aleksandra; Gajek, Jacek; Mysiak, Andrzej (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
We report a case of a 65-year-old female patient after replacement of aortic and mitral valve with mechanical prostheses and implantation of a pacemaker hospitalized in our clinic due to acute coronary syndrome complicated with cardiac arrest due to ventricular fibrillation. The electrocardiogram performed on admission showed signs of myocardial infarction with concomitant ventricular pacing. After successful resuscitation the coronary angiography was performed, which showed occlusion of the left circumflex artery (LCx) by thrombus. On the basis of intravascular ultrasound imaging the presence of vulnerable plaque, parietal thrombus and dissection of LCx were excluded. It suggested that occlusion of the LCx resulted from its embolism by left-sided heart thrombus due to subtherapeutic oral anticoagulation. In this case suboptimal anticoagulation was partially iatrogenic. Two weeks before the patient had been given vitamin K intravenously due to indeterminable international normalized ratio (INR) level, which caused transient resistance to oral anticoagulants. This case report illustrates tragic difficulties in the treatment with vitamin K antagonists, which concern as many as 2/3 of anticoagulated patients. These troubles contributed to the search for new, more efficient and safer anticoagulants. There are two classes of new oral anticoagulant drugs, which do not require monitoring of coagulation: direct thrombin inhibitors (e.g. dabigatran) and factor Xa inhibitors (e.g. rivaroxaban). In spite of their proven efficacy in the prevention of ischaemic stroke related to atrial fibrillation and prevention or treatment of deep vein thrombosis and pulmonary embolism, the use of new oral anticoagulants for the treatment of patients with mechanical valve prostheses needs further research.